The acceptance and adoption of green farming among SMEs in Melaka / Ikram Idris - Idris, Ikram (Faculty of Business and Management, 2012)
This study was conducted to examine the Acceptance and Adoption of Green Farming Technology among SMEs in Melaka. Researcher has conducted the study by giving the survey to the farmer in Melaka. There are four variables that have been test by the researcher and the variables are shared belief, trust, training and project communications. This variable will be used to examine the acceptance and adoption of Green Farming. The researcher was giving the questionnaires to the farmer to answer. The findings from the study found that facility can affect to acceptance and adoption of Green Farming Technology toward the farmer.